(untitled) (African Disability Rights Yearbook, 2025)
The Central Bank of Nigeria introduced the National Financial Inclusion Strategy in 2012 to tackle financial exclusion and push back on the barriers that debar financial access in Nigeria. Subsequently, women, youth, rural dwellers, and persons in the North-East and North-West of Nigeria, who represent the most excluded societal segments, have been the focus of financial inclusion laws, policies, and initiatives. One group of persons, however, that seems to be overlooked and not adequately catered for by financial inclusion laws, policies and interventions are persons with disabilities. This article examines the challenges of accessing and using financial services for persons with disabilities as well as the regulatory framework for financial inclusion in Nigeria. The article further elucidates the criticality of financial services for persons with disabilities whilst highlighting the negative impacts of lack of access to finance. It finds that persons with disabilities are confronted with multidimensional difficulties due to the inadequacy of laws to advance financial access to them. Seven recommendations are proffered by the authors. These are to: strengthen relevant laws and institutions; tailor financial services to the needs of persons with disabilities; prioritise accessibility as a minimum benchmark for financial services; improve staff training for financial service providers; foster stakeholder collaboration; promote enforcement and implementation of laws; and adopt monitoring and evaluation mechanisms. It is expected that these recommendations will demonstrate the gap in the legal framework on financial access for persons with disabilities and the attendant need for ameliorating policy initiatives.